Sie sind auf Seite 1von 2

# 1cos 4 x Dx ( senx ) =cosx 1 n cos n1 xsenx n1

## cos 2 x sen2 x= Dx ( se n1 x ) = cos x= + cos n2 x

8 Dx ( cosx )=senx 1x 2
n n
2 1cos 2 x Dx ( tanx ) =sec 2
x 1 n1
sen xcosx n1
sen x= 1
Dx ( cos x )= sen n
x= + senn 2 x
2 Dx ( cotx ) =csc 2 x
2 1+ cos 2 x
1x 2
n1
n n
cos x= Dx ( secx )=sec xtan x 1 tan x
tan n2 x
1 n
2 Dx ( tan x )= tan x=
2 2
Dx ( cscx )=cscxcotx 1+ x
2
n1
tan x=sec x1 cot n1 x
x= tan x +1 2 tanx =ln ( secx)
Dx ( cot
1
x ) =
1
cot n
x= cot n2 x
cotx=ln ( sen x) 1+ x 2
n1
sec 2 1 n sec n 2 xtanx n2
2
csc x=cot x +1 2
secx=ln
( Dx (
secx+tanx) s ec1
x ) = sec x=
n1
+
n1
sec n2 x
x x 1
2
cos (t + s ) +cos(cscx=ln
ts) ( cscxcotx) n2
sen (t ) sen ( s )= 1 csc xcotx n2
2 sec 2 x=tanx
1
Dx ( cs c x )= csc n x=
n1
+
n1
cscn2 x
x x 1
2
cos ( t+ s ) +cos (ts)2
cos t cos s =
( ) ( )
2
csc x=cotx
secxtanx=secx senm1 xco s n+1 x m1
cos ( t ) sen ( s )=
sen ( s +t )+ sen (st)
m
sen xco s x= n
m+ n
+
m+ n
senm2 x cos
2 cscxcot =cscx
se n1 x=xse n1 x +1x 2 tan2 x=tanxx senm +1 xco sn1 x n1
sen m xco s n x=
m+ n
+
m+ n
senm x cos n
cos1 x=xco s1 x 1x 2 cot 2 x=cotxx
tan1 x=xta n1 x 1+x 2
cot1 x=xco t1 x +ln 1+ x2
x + x 21
sec1 x=xse c1 xln
x+ x 21cos
1 4 x Dx ( senx ) =cosx 1 n cos n1 xsenx n1
cos 2 x1
sen2 x= 1 Dx ( se n1 x ) = cos x= + cos n2 x
csc x=xcs c 8
x+ ln Dx ( cosx )=senx 1x 2
n n
2 1cos 2 x Dx ( tanx ) =sec 2
x 1 n1
sen xcosx n1
sen x= 1
Dx ( cos x )= sen n
x= + senn 2 x
2 Dx ( cotx ) =csc 2 x
1+ cos 2 x
1x 2
n n
cos x=
2
Dx ( secx )=sec xtan x 1 tan n1 x
tan n2 x
1 n
2 Dx ( tan x )= tan x=
2 2
Dx ( cscx )=cscxcotx 1+ x
2
n1
tan x=sec x1 cot n1 x
x= ta n x +12 tanx =ln ( secx)
Dx ( cot
1
x ) =
1
cot n
x= cot n2 x
cotx=ln ( sen x) 1+ x 2
n1
sec 2 1 n
n 2
sec xtanx n2
2
csc x=cot x +1 2
secx=ln
( secx Dx (
+tanx)s ec1
x ) = sec x=
n1
+
n1
sec n2 x
x x 1
2
cos (t + s ) +cos(cscx=ln
ts) ( cscxcotx) n2
sen (t ) sen ( s )= 1 csc xcotx n2
2 sec 2 x=tanx
1
Dx ( cs c x )= csc n x=
n1
+
n1
cscn2 x
x x 1
2
cos ( t+ s ) +cos ( ts)2
cos t cos s =
( ) ( )
2
csc x=cotx
m1 n+1
secxtanx=secx sen xco s x m1
cos ( t ) sen ( s )=
sen ( s +t )+ sen (st)
m
sen xco s x= n
m+ n
+
m+ n
senm2 x cos
2 cscxcot =cscx
se n1 x=xse n1 x +1x 2 tan2 x=tanx x senm +1 xco sn1 x n1
sen m xco s n x=
m+ n
+
m+ n
senm x cos n
cos1 x=xco s1 x 1x 2 cot 2 x=cotxx
tan1 x=xta n1 x 1+ x 2
cot1 x=xco t1 x +ln 1+ x2
x + x 21
sec1 x=xse c1 xln
x+ x 21
csc1 x=xcs c 1 x+ ln
Caso 1 a2x 2
a
x
cos
sen

a x
x
cos x
tan
sen a
sec a
sec
tan